Boccia court analisys for real-time scoring - Leite, Pedro (2018)
This paper aims to develop a tool to increase the engagement and commitment of the elderly population in the Boccia game. This tool is based on the implementation of a real-time computer vision algorithm that analyses the Boccia court field and displays the score in a graphical user interface. In Portugal, physical inactivity is associated with 14% of deaths per year, higher percentage than the world average, which is less than 10%. In this paper, the Boccia game is used for promoting physical activity in the elderly, due to its simplicity and adaptability to their physical impairments. This system intends to encourage the elders to lead a more active lifestyle, providing a healthier life and possibly reducing the risk of major diseases and injuries.